MENCIPTAKAN PEMBELAJARAN FUN LEARNING BASED ON SCIENTIFIC APPROACH DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK PADA PEMBELAJARAN PAI - Layyinah, Leni (TARBAWY : Indonesian Journal of Islamic Education, 2017)
Nowadays, Indonesian education is posed with the increasing challenges of the third millennium. One of the infrastructures in Indonesia is school. A rigid school will not be a good learning place, because children only go to school without learning. In teaching and learning process, teachers should be aware that education is not merely about teaching. Instead, it is about how teachers should be able to create a fun learning atmosphere and implement the subject of Islamic Education by not only teaching religious knowledge but also directing students and forming their characters. The research took Equal Bright Primary School in Bandung as sample of an international-standard school promoting Multiple Intelligences. The analysis of the data on each aspect of instructional strategies reveals certain uniqueness in the teaching and learning process implemented in Equal Bright, which is full of fun and very interesting. The implementation of fun learning strategy through scientific approach plays a vital role in exploring student’s potentials. The birth of this strategy gives a great expectation for the birth of the future generation with good quality and mentality to compete in the global arena. Equal Bright is an education institution implementing the method of multiple intelligences holistically, in which students are accommodated according to their learning and thinking styles. In implementing the fun learning strategies through scientific approach, the teaching and learning process can be more active, creative, effective, and fun.